Current status, research trends, and challenges in water electrolysis science and technology. (2nd October 2020) - Grigoriev, S.A.; Fateev, V.N.; Bessarabov, D.G.; Millet, P.
Abstract: Water electrolysis has various industrial applications. Over the past years, interest in water electrolysis technologies has increased largely due to the renaissance of the nuclear-hydrogen energy concept and also the prospect of the large-scale implementation of power plants based on renewable energy sources. The purpose of this paper is to present a brief review of the state-of the-art in the field of water electrolysis science and technology, including a description of the various water electrolysis technologies, and a discussion of the associated challenges and opportunities. The three main types of water electrolyzers – alkaline, proton exchange membrane, and solid oxide – are considered and described. Their electrochemical performances and limitations are presented and analyzed. Some cost elements are also reported. Research trends in the field are discussed. Possible solutions for performance improvements are offered. The paper concludes with a discussion of several perspectives in terms of future applications. Highlights: Current status, research trends and challenges in water electrolysis are discussed. Alkaline, proton exchange membrane and solid oxide electrolyzers are considered. Electrochemical performances and limitations are presented and analyzed. Cost components and several perspectives of future applications are reported. Possible solutions for performance improvements are discussed.